Industrial Waste Management through Material and Energy Recovery: The Case of Hwange Power Station, Zimbabwe - Jerie, Steven; Jenya, Baldwin (Iranian Journal of Health, Safety and Environment, 2022)
The aim of this study was to examine industrial waste minimisation through material and energy recovery at Hwange Power Station in Zimbabwe. This project is significant in that it envisages the opportunities of boosting power output through the use of industrial waste management at international and national levels. Most industries in Zimbabwe are facing challenges in the sustainable waste disposal and the nation at large is experiencing severe power shortages. A detailed descriptive study was undertaken to analyse the potential of boosting power output whilst sustainably managing industrial waste. The research administered 200 questionnaires which are approximately 30% of the entire population directly involved in the core waste generating activities. Out of the 200 questionnaires that were administered, a total of 182 were completed and returned in time for data compilation giving a response rate of 88.5%. The qualitative and quantitative research designs were used with direct field observations, interviews and questionnaires as primary sources of data. Secondary data was acquired from existing literature to boost and support the research findings. The main findings of the research divulged the types and quantities of waste from power generation activities, the effectiveness of the current methods of waste management and the definitive degree of waste management through material and energy recovery at Hwange Power Station. The study also revealed that energy and material recovery are essential methods of industrial waste management as well as opportunities for boosting power output. It was therefore recommended that Hwange Power Station needs to consider investing in energy recovery to boost power output at the same time sustainably managing waste